The Relationship of Medication Adherence to Controlled HbA1c and ASCVD Risk in Type II Diabetes Mellitus Patients in Minggir Primary Health Care - Aquina Nino Rama Dhanti Dewita; Phebe Hendra; Dita Maria Virginia (Sanata Dharma University, 2025)
Type II diabetes mellitus (DM) therapy can be evaluated from the controlled HbA1c. Another aspect that needs to be controlled in patients with DM is lipid levels. Lipid levels should be controlled in a patient with type II DM to prevent atherosclerotic cardiovascular disease (ASCVD). The study was conducted to determine the relationship between medication adherence with controlled HbA1c and ASCVD risk in patients with type II DM. The study was an analytical observational study with a cross-sectional research design used to examine the relationship between medication adherence with controlled HbA1c and ASCVD risk. Our respondents were patients following a chronic disease management program at Minggir Primary Health Care. The level of medication adherence was measured using the Medication Adherence Report questionnaires. The ASCVD risk was measured using the American College of Cardiology/American Heart Association tools. The chi-squared test was applied to determine the relationship between medication adherence with HbA1c values and ASCVD risk in patients with type II DM. Most patients with type II DM had high medication adherence (60%), controlled HbA1c values (56.4%), and high ASCVD risk (70.9%). There was no significant relationship between medication adherence in type II DM patients with controlled HbA1c values and ASCVD risk.